Water flow and temperature as main factors that regulate phytoplankton and cyanobacterial blooms in a large subtropical river (INNOTEC, 2020)
Seasonal variations and interannual changes (2006-2019) of the phytoplankton community, related to variations in water quality and river discharge, in the lower part of the Uruguay River in South America are presented. In total, 422 microalgae and cyanobacterial taxa were identified. Cryptophytes, cyanobacteria, and diatoms were the most important groups. Although nanoflagellates and cryptophytes were always present in plankton, statistical differences were found in seasonal assemblages of phytoplankton. According to the similarity analysis (SIMPER), the typical species for each season were identified: Aulacoseira spp. in winter, Dolichospermum uruguayense, Durinskia baltica and Ankistrodesmus arcuatus in spring, Microcystis aeruginosa, M. wesenbergii, Dolichospermum uruguayense and D. circinale in summer and Ceratium cf. furcoides, A. arcuatus, Raphidiopsis and Jaaginema sp. in autumn. Under lentic river conditions (
Keywords: harmful algal blooms; large rivers; Río de la Plata; diversity